Adopting agile approach: A case in Malaysia - Omar, Mazni; Syed-Abdullah, Sharifah-Lailee; Yasin, Azman (2010)
Agile methodology continues to evolve due to business and technological demands.However, there are few studies reported related to encouraging new organizations to adopt agile practices especially in Asian countries.This paper presents the initial findings from an action research study on agile-extreme programming (XP) adoption amongst software engineering (SE) teams.The results showed that the agile-XP approach received positive feedbacks amongst team members during the software project, even though the level of adoption was mixed.These findings offer valuable insights into aspects related to agile approach to suit an organizational culture.